2022
DOI: 10.1007/s00526-022-02222-7
|View full text |Cite
|
Sign up to set email alerts
|

A quasiconformal Hopf soap bubble theorem

Abstract: We show that any compact surface of genus zero in $${\mathbb {R}}^3$$ R 3 that satisfies a quasiconformal inequality between its principal curvatures is a round sphere. This solves an old open problem by H. Hopf, and gives a spherical version of Simon’s quasiconformal Bernstein theorem. The result generalizes, among others, Hopf’s theorem for constant mean curvature spheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In [10], the first two authors showed the converse statement, i.e., that any C 2 ovaloid in R 3 that satisfies the Weingarten inequality must be totally umbilic along four disjoint great semicircles. For other uniqueness theorems of ovaloids, or immersed spheres in R 3 , satisfying the Weingarten inequality, see [8,11,12,13,20].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…In [10], the first two authors showed the converse statement, i.e., that any C 2 ovaloid in R 3 that satisfies the Weingarten inequality must be totally umbilic along four disjoint great semicircles. For other uniqueness theorems of ovaloids, or immersed spheres in R 3 , satisfying the Weingarten inequality, see [8,11,12,13,20].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Bryant [Br] studied closed SW-surfaces using complex analysis. More recently many new results and examples about Special Weingarten surfaces were produced by different authors [AlEsGa,BuOr,CaCa,CoFeTe,EsMe,FeGaMi,GaMaMi,GaMi1,GaMi2,GaMiTa,KuSt,SaTo1,SaTo2]. We point out that, in most of the cited works, W is expressed in terms of the mean curvature H and the Gaussian curvature K, resulting in the symmetry of W with respect to the principal curvatures.…”
Section: Introductionmentioning
confidence: 93%
“…The question of what values of umbilic slope are possible on various spheres is an area of active research [11] [5]. The derived Codazzi-Mainardi equation (2.3) is a necessary integrability condition for a C 3 -smooth surface to be rotationally symmetric and has some striking consequences in this direction, two of which are the following proposition and theorem.…”
Section: Rotationally Symmetric Surfacesmentioning
confidence: 99%